PENGARUH KONFLIK DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN DI PT.ANUGRAH TOUR SEMESTA JAKARTA - Abdul Latif; Prawoto (Human Capital Development, 2016)
Purpose- The purpose of this study was to determine effect of conflict and job satisfaction on the performance of employees in PT.Anugrah Tour SemestaJakarta. Design/methology/approach- This primary research conducted over 3 months of May to July 2016. The study is in use accidental sampling and immediately gave questionnaires to 20 respondents from 80 respondents. This study used multiple linear regression to analyze the research data. Findings- The results showed that: (1) the conflict have a positive influence and significant impact on the performance of employees (2) job satisfaction has a significant influence on employee performance and (3) conflict and job satisfaction simultaneously positive and significant effect on the performance of employees at PT. anugrah Tour Semesta Research limitations- The limited variables included in this research Practical implications- The problem of latent conflicts shall be soulved immediately